SIGNIFIKANSI KAJIAN BUDAYA BAGI PENGEMBANGAN ILMU-ILMU HUMANIORA - St. Sunardi (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
Cultural studies in the development of humanities studies is now in a problematic position, if not the opposite. While cultural studies pivot on the practice of meaning in the context of change, humanities sciences nowadays dwell on the mastery of knowledge and skills. It tends to forget its original purpose as studies that aim to humanize humans. To resolve this problem so that both have creative power, the humanities studies must have the courage to present the studies in three-channel mode, namely political, textual and post-disciplinary. Meanwhile, to preserve its anticipatory power, cultural studies must no longer shy to enter the territory of aesthetics and ethics in its studies.